Strong Parallel Differential Gene Expression Induced by Hatchery Rearing Weakly Associated with Methylation Signals in Adult Coho Salmon (O. kisutch). (11th March 2022) - Leitwein, Maeva; Wellband, Kyle; Cayuela, Hugo; Le Luyer, Jérémy; Mohns, Kayla; Withler, Ruth; Bernatchez, Louis
Abstract: Human activities and resource exploitation led to a massive decline of wild salmonid populations, consequently, numerous conservation programs have been developed to supplement wild populations. However, many studies documented reduced fitness of hatchery-born relative to wild fish. Here, by using both RNA sequencing and Whole Genome Bisulfite Sequencing of hatchery and wild-born adult Coho salmon ( Oncorhynchus kisutch ) originating from two previously studied river systems, we show that early-life hatchery-rearing environment-induced significant and parallel gene expression differentiation is maintained until Coho come back to their natal river for reproduction. A total of 3, 643 genes differentially expressed and 859 coexpressed genes were downregulated in parallel in hatchery-born fish from both rivers relative to their wild congeners. Among those genes, 26 displayed a significant relationship between gene expression and the median gene body methylation and 669 single CpGs displayed a significant correlation between methylation level and the associated gene expression. The link between methylation and gene expression was weak suggesting that DNA methylation is not the only player in mediating hatchery-related expression differences. Yet, significant gene expression differentiation was observed despite 18 months spent in a common environment (i.e., the sea). Finally, the differentiation is observed in parallel in two different river systems, highlighting the fact that early-life environment may account for at least some of the reduced fitness of the hatchery salmon in the wild. These results illustrate the relevance and importance of considering both epigenome and transcriptome to evaluate the costs and benefits of large-scale supplementation programs.